KAJIAN KUAT TEKAN BETON SELF COMPACTING CONCRETE HASIL PENGEBORAN INTI VARIASI PENGAMBILAN ARAH VERTIKAL DAN HORIZONTAL - Valentana Ardian Tarigan; Immanuel Panusunan Tua Panggabean (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2020)
Buildings that use concrete as a structural material are faced with certain compressive strength requirements that are used as design standards. It is a fact that is always found in the field that the quality of the installed concrete cannot always be maintained at the target quality standard. The regulation that becomes the reference for Indonesian concrete standards, namely SNI 2847: 2013 requires that the test standard of core drilling is if the certainty of the low compressive strength value of concrete is known and the calculation results show that the load-bearing capacity is significantly reduced, then the core concrete test (cores) is allowed. taken from the area in question according to ASTM C42M. In such cases, three specimens shall be taken for each compressive strength test which falls below the given value. The test was carried out using a diameter of 4 "and a diameter of 3", respectively, 3 (three) pieces of the core specimen were taken in horizontal and vertical directions. The test results obtained by an average of the three specimens from each variable are as follows, the compressive strength of the concrete taking the core test object in the vertical direction of diameter 4 "is 35.96 MPa, diameter 3" is 32.97 MPa, the compressive strength of the concrete taking the core test object direction horizontal diameter 4 "is 22.93 MPa, diameter 3" is 20.35 MPa. Comparator of the 4 "concrete mixture that was formed produced an average compressive strength of 37.65 MPa.